Komunikasi Antar Pribadi dalam Hubungan Berpacaran yang Menimbulkan Konflik Kekerasan Psikis - Aisyah Anjani; Sri Budi Lestari (Interaksi Online, 2018)
Interpersonal communication does not always go well, that is why conflicts arise. Likewise in dating relationships which often experienc conflicts due to lack of quality of communication. Some dating relationships, if the conflict cannot be resolved, will lead to psychological violence. This shows how important interpersonal communication is in managing conflict. This research is interesting to study because the importance of interpersonal communication is used to manage conflicts in dating relationships. This study aims to describe Interpersonal Communication in Dating Relationships which Causes Psychological Violence Conflict. Using a qualitative descriptive study approach with data collection carried out by in-depth interviews. The research subjects were three women who had experienced psychic violence in dating. The theory used is argumentativeness, assertiveness, and verbal aggressiveness theory. The results of this study indicate that the three informants show mutual comfort with closeness and intimacy in their relationships, but there is a feeling of unworthiness that causes excessive dependence on closeness and intimacy that can lead to feelings of discomfort. Individuals feel afraid of being abandoned by their partners and usually overly monitor their relationships with their partners and in this category extreme emotions and low levels of trust. Conflict also often occurs based on jealousy and lack of communication quality. Conflict management efforts that have been carried out are not effective so that problems cannot be resolved properly and occur repeatedly. Even victims of psychic violence because of their own pressure can turn into psychic violence perpetrators as a reaction.